Pelatihan Usaha Budidaya Tanaman Sayuran Dengan Teknik Hidroponik - Suharno Suharno; Farmawaty Farmawaty; Irma Rahayu; Rahmad S. Budi; Puguh Sujarta; Linus Y. Chrystomo; Ign. Joko Suyono (Bakti Hayati: Jurnal Pengabdian Indonesia, 2022)
Food crop cultivation, such as vegetables, is one of methods to reach food security goals. There are lots of methods to cultivate vegetables, and one among them is hydroponic cultivation. Our activities aimed to introduce this hydroponic cultivation technology to the community in SMA Negeri 2 Skanto, District of Keerom,Â  Jayapura. The methodology used this time was technology transfer by sharing information to the students as targeted community. The high enthusiasm from participants became an indicator for the successful of this program.Keyword: cultivation; food security; vegetables; hydroponic.Â